Morphological and molecular characterization of nanche (Byrsonima crassifolia L.) native of Nayarit, Mexico - López-Guzmán, Graciela Guadalupe; Balois-Morales , Rosendo; Bautista-Rosales, Pedro Ulises; Jiménez-Zurita, Jose Orlando (Ecosistemas y Recursos Agropecuarios, 2023)
ABSTRACT. The nanche (Byrsonima crassifolia (L.) H.B.K) belongs to the Malpighiaceae family. The genus Byrsonima has a noetropical distribution and is highly diverse with more than 100 species. The objective of this work was to characterize the morphological and genetic variability of the native nanche fruit. The work was carried out during the year 2020, a collection was made in commercial orchards in San Lorenzo (SL’s), municipality of Ruiz, Nayarit, a morphological, physicochemical and molecular characterization was carried out, the statistical analysis was carried out with the package (SAS) ver.9.0 and the genetic data were analyzed with the GenAlEx software. The SL-4 and SL-8 genotypes (cultivated) and the native NAT-5 and NAT-6, are selected by the producer, who opts for the following characteristics: large, sweet, bittersweet or sour nanche, and yellow in color. Eight ISSRs microsatellite markers were found with which polymorphism is obtained, the cluster analysis formed four groups with the 15 nanche accessions, the number of alleles was seven maximums, the expected heterozygosity (He) was obtained in a range of 0.58- 0.62, which is a measure of genetic diversity, these indices indicate high genetic diversity of nanche in the municipalities of Nayarit.